Targeting Neuroinflammation in Neovascular Retinal Diseases - Wang, Tianxi; Tsirukis, Demetrios I.; Sun, Ye (Frontiers in Pharmacology, 2020)
Retinal blood vessels provide the necessary energy, nutrients and oxygen in order to support visual function and remove harmful particles from blood, thus acting to protect neuronal cells. The homeostasis of the retinal vessels is important for the maintenance of retinal visual function. Neovascularization is the most common cause of blindness in patients with retinopathy. Previous studies have shown that inflammatory mediators are known key regulators in retinopathy, but their causal link has been elusive. Although inflammation is often thought to arise from inflammatory cells like macrophages, neutrophils, and resident microglia, retinal neurons have also been reported to contribute to inflammation, through inflammatory signals, which mediate blood vessel growth. Therefore, it is important to explore the detailed mechanisms of neuroinflammation’s effects on retinal neovascularization. This review looks to summarize current research on the relationship between retinal angiogenesis and neuroinflammation in retinopathy, as well as the potential effects of neuroinflammation on retinal neovascularization in different animal models.